Testosterone and Adipokines are Determinants of Physical Performance, Strength, and Aerobic Fitness in Frail, Obese, Older Adults - Lina E. Aguirre; Irum Zeb Jan; Kenneth Fowler; Debra L. Waters; Dennis T. Villareal; Reina Armamento-Villareal (International Journal of Endocrinology)
In this study, we evaluated the independent and combined effects of baseline circulating gonadal, anabolic hormones and adipokines on physical function in 107 frail, obese (BMI ≥ 30 kg/m2), and older (≥65 yr) subjects. Our results showed significant positive correlations between circulating testosterone and insulin growth factor-1 (IGF-1) with knee flexion, knee extension, one-repetition maximum (1-RM), and peak oxygen consumption (VO2 peak), while no correlation was observed with estradiol. Among the adipokines, high sensitivity C-reactive protein (Hs-CRP) and leptin negatively correlated with the modified physical performance testing (PPT), knee flexion, knee extension, 1-RM, and VO2 peak. Interleukin-6 ( Il-6) negatively correlated with knee flexion and VO2 peak and soluble tumor necrosis factors receptor-1 (sTNFr1) correlated with PPT, 1-RM, and VO2 peak. Adiponectin correlated negatively with 1-RM. Multiple regression analysis revealed that, for PPT, sTNFr1 was the only independent predictor. Independent predictors included adiponectin, leptin, and testosterone for knee flexion; leptin and testosterone for knee extension; adiponectin, leptin, and testosterone for 1-RM; and IGF-1, IL-6, leptin, and testosterone for VO2 peak. In conclusion, in frail obese older adults, circulating levels of testosterone, adiponectin, and leptin appear to be important predictors of physical strength and fitness, while inflammation appears to be a major determinant of physical frailty.